A Cost benefit analysis of vocational education and training in Rwanda - JEON, Inhyeong (KDI School, 2016)
This paper evaluates the technical vocational education and training (TVET) project, using cost-benefit analysis. The project was financed by KOICA for Rwanda from 2010 to 2011. By testing two alternative programs, the paper tries to find which program is more effective. The two alternative programs are: one is three-year College of technology program (CoT) at the post-secondary level; and the other one, one-year vocational training course (VTC), taking in youth with all educational background. The results turn out that VTC and CoT, both are not economic viable although CoT is more desirable than VTC. It is tested by lifetime earning of graduates from each program. We also check the changes in income, drop-out rates and discount rate by sensitivity analyses. No matter how we change dropout rates, the result doesn’t change. Above all, it’s important to find the factors what makes the programs ineffective, and then remove the reason so as to improve the program for reducing unnecessary spending.
Thesis(Master) --KDI School:Master of Development Policy,2016